Legal Review on Foreign Investment In Indonesia - Indriastuti, Lusia (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Law Number 25 Year 2007 is the investment law of Indonesia which replacesLaw Number 1 year 1967 on Foreign Investment and Law Number 5 year 1968 onDomestic Investment. This new law no longer distinguishes foreign and domesticinvestment. The formation of law Number 25 Year 2007 is the commitment ofIndonesia upon ratification of the (WTO Agreement).Government policy in regulation of capital investment and investment inIndonesia is more important to increase investor interest in Indonesia. Because ofthis law, capital market development required in order to realiting legal certainlyinvestment. Legal certainty can be realized through a regulation of good andclear, so that will be clear also its application.Keywords : legal certainty, investment law.